Implementasi Konsep Arsitektur Fleksibel pada Desain Pasar Berumur Panjang - Faiz Ramadiansyah; I Gusti Ngurah Antaryama; FX Teddy Badai Samodra (Universitas Sebelas Maret Surakarta, 2023)
The market should have flexibility in its use. This study aims to design a market that has high flexibility. Highly flexible market design aims to create a longer market life, more adaptive to future changes, and a market that can contract and expand as needed. The flexible marketplace will be designed using a concept-based framework method. This method describes abstract ideas in a flexible market form. Then, abstract ideas are processed starting from making hypotheses, perfecting, mapping, proposing moments, arranging elements, and proposing. The results show that the proposed design is capable of forming a flexible market that applies flexible architectural principles, such as adaptive market space, retractable market roof, and mobile stalls.